Systems of suffering : dispersal and the denial of asylum - Darling, Jonathan (Pluto Press, 2020)
Of the many state-enacted cruelties to which refugees and asylum seekers are subjected, detention and deportation loom largest in popular consciousness. But there is a third practice, perpetrating a slower violence, that remains hidden: dispersal. In Systems of Suffering, Jonathan Darling provides the first detailed account of how dispersal-the system of accommodation and support for asylum seekers and refugees in the UK-in fact both sustains and produces patterns of violence, suffering and social abjection. Darling explores the evolution of dispersal as a privatized process, from the first outsourced asylum accommodation contracts in 2012 to the renewed wave of outsourcing pursued by the Home Office today. Drawing on five years of research into the UK's dispersal system, and foregrounding the voices and experiences of refugees and asylum seekers, Darling argues that dispersal has played a central role in the erasure of asylum from public concern. Systems of Suffering will prove a vital tool in the arsenal of those fighting to hold the government to account for the violences of its asylum policy and practice.